Role of safe space in improving menstrual awareness and menstrual hygiene practices among adolescents in Zamfara: a case study of REACH project intervention - Lawali, Yakubu; Bello, Murtala; Hussaini, Rahinatu Adamu; Jongshwan, Chanan Solomon (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Menstrual awareness and hygiene practices have been a challenge for adolescent girls in African countries and Nigeria inclusive which subsequently affects their health, and wellbeing. The aim of the study was to evaluate the effects of REACH project intervention in improving knowledge and practice of menstrual care among adolescent girls. Methods: A post-test only non-equivalent groups quasi-experimental design was adopted with Kaura Namoda and Talata Mafara as the intervention Local Government Authorities (LGAs) and Bungudu and Maru as the control LGAs conducted between August 2021 to October 2021. Quantitative approach was employed using self-developed questionnaire for data collection. Multi-stage sampling technique was used. A total of 400 questionnaires were administered with 200 each for control and intervention LGAs. Results: The result of the study shows that, adolescents in the REACH Project intervention communities have higher level of awareness and more likely to practice menstrual hygiene as compared to non-REACH intervention communities. Therefore, it is recommended that, safe space strategies should be adopted in any matters related to adolescents sexual and reproductive health. Conclusions: Safe space is effective in improving adolescents sexual and reproductive health.